Rising star mathematics: year 2, pupil textbook - Low, Emma (Rising Stars UK, 2022)
This mathematics textbook provides a comprehensive exploration of fundamental concepts across various branches of math, including arithmetic, algebra, geometry, and statistics. Designed for students at different levels, the textbook emphasizes problem-solving strategies and critical thinking skills through clear explanations and practical examples. Each chapter includes exercises that reinforce learning and encourage application of concepts. With a focus on real-world relevance, this textbook aims to build a strong mathematical foundation, preparing students for advanced studies and everyday problem-solving.